Literature Review: Differences in the Level of Satisfaction of BPJS Patients and General Patients on the Quality of Health Services - Sri Mulyani; Susilawati (Pena Cendekia Insani, 2022)
Satisfaction is something that is used in a role model as a determinant of the success of a service program that involves patient expectations for officers to provide good and fair health services, not discriminating between patients, both BPJS users and general patients, must be treated equally. The method used in this study is the literature review method which in collecting journals uses Google Schoolar published in the last 5 years. The database search used was Google School, and found 4 journal articles that matched the inclusion. The results of the literature review show that there are differences in satisfaction where BPJS patient satisfaction is lower than general patient satisfaction. The difference in satisfaction between BPJS patients and general patients can be used as evaluation material for health service providers so that there are no longer differences in patient satisfaction levels. Every patient has the right to get the same health services according to their medical needs